Efficacy and safety of high-dose chemotherapy as the first or subsequent salvage treatment line in patients with relapsed or refractory germ cell cancer: an international multicentric analysis - Seidel, Christoph; Schaefers, C.; Connolly, E. A.; Weickhardt, A.; Grimison, P.; Wong, V.; De Giorgi, U.; Hentrich, M.; Zschäbitz, Stefanie; Ochsenreither, S.; Vincenzi, B.; Oing, C.; et al. (ESMO open, 2024)
Background - In relapsed or refractory (RR) metastatic germ cell cancer (GCC), high-dose (HD) chemotherapy (CTX) plus autologous stem cell transplantation is considered the standard of care. Limited data exist regarding the efficacy of HD-CTX following conventionally dosed salvage regimens (CDRs). This analysis explores and contrasts the efficacy of HD-CTX as the first or subsequent salvage regimen. - Patients and methods - Data were retrospectively collected to explore the efficacy of HD-CTX administered as the first (group A) or subsequent salvage CTX (group B) after a CDR. The primary endpoint was OS from the time of HD-CTX. Associations of survival, overall response rate (ORR), and toxicity with clinical characteristics were explored using stratified Kaplan-Meier and Cox regression models. - Results - Overall, 283 patients with GCC were included from 11 international centers, with 159 patients (56%) in group A and 124 patients (44%) in group B. The first salvage treatment was administered between 1998 and 2022, with a median follow-up of 27.0 [standard deviation (SD) 46.2] months for group A and 17.0 (SD 48.5) months for group B. The median OS from HD-CTX treatment initiation was not reached in group A, compared with 25 months in group B (P = 0.00027), associated with 2- and 5-year OS rates of 74% and 63% (group A) versus 53% and 37% (group B), respectively. When administered as the first salvage treatment, HD-CTX was associated with a higher ORR (79% versus 60%; P = 0.013) and lower nonhematologic grade ≥3 toxicity rate (78% versus 97%; P < 0.001). Concerning risk factor analysis for the total cohort, the International Prognostic Factors Study Group score was the only independent predictor of OS in multivariable analysis (P = 0.006). - Conclusions - When administered as the initial salvage treatment or after CDR, HD-CTX exhibits curative potential for patients with RR GCC. The efficacy and safety outcomes were more favorable when HD-CTX was conducted as the first salvage treatment line.